Neuroticism moderates the association between beliefs about medications and reported adverse medication effects in mild cognitive impairment. (December 2021) - Kelly, Dana A; Davis, Jennifer D; Daiello, Lori A; Burke, Erin M; Fernandez, Tiana; Tremont, Geoffrey; Ott, Brian R; Margolis, Seth A
Abstract: Background: Adverse medication effects may negatively affect quality of life (QoL), treatment adherence, and tolerability/enrollment in investigational drug studies. No research has investigated whether negative beliefs about medications and personality influence adverse effect reporting in people with Mild Cognitive Impairment (MCI), where disease modifying therapies are needed. We examined associations among medication beliefs, neuroticism, and perceived adverse medication effects in people with MCI. Method: Participants (N=50, age: 72±7 years, 54% female) with MCI completed the Beliefs about Medicines Questionnaire (BMQ: Harm and Necessity‐Concerns [N‐C] subscales), NEO Five‐Factor Inventory‐3 (Neuroticism), and Generic Assessment of Side Effects (GASE: adverse effect count and intensity). Correlations and ordinary least squares (OLS) regression assessed interrelationships. The moderating effect of neuroticism on the association between medication beliefs and adverse effect reporting was modeled at mean±1 standard deviations of neuroticism. Result: Participants took an average 6±3 medications/day; 20% took anti‐dementia medications. The number of reported adverse effects per participant ranged from 0‐15 (X̅=4). On average, adverse effect intensity was rated as mild; however, 26% endorsed moderate‐to‐severe intensity. On average, participants did not believe medications were generally harmful. Yet, 30% indicated that concerns about their specific medications outweighed perceived necessity of treatment. Neuroticism was normally distributed. Higher neuroticism and stronger harm/concern beliefs correlated with adverse effect intensity (Neuroticism: r =0.378, p =0.007; Harm: r =0.315, p =0.026; N‐C: r =‐0.406, p =0.003). OLS regression models including neuroticism and Harm or N‐C beliefs (run separately) each accounted for 32% of the variance in adverse effect intensity. There was an interaction between medication beliefs and neuroticism ( p's ≤0.04); stronger harm beliefs and concerns outweighing necessity beliefs corresponded to greater adverse effect intensity at average and above average neuroticism (Harm: β=0.90, p =0.01; N‐C: β=‐0.33, p =0.003 and Harm: β=1.76, p =0.001; N‐C: β=‐0.58, p =0.001, respectively) but not at low‐average levels. Neither model was associated with raw adverse effect count. Conclusion: Individuals with MCI who are more stress‐reactive (neurotic) and maintain negative beliefs about medications tend to endorse more intense adverse effects. Supportive approaches aimed at helping stress‐reactive patients manage negative beliefs, reactions, and expectations about medications may enhance QoL, improve treatment adherence, and impact willingness to participate in clinical trials.